Perencanaan Sistem Informasi Strategis Menggunakan Model Ward and Peppard (Studi Kasus : Klinik Yulia Asniati) - Arif Prambayun; Putri Maharani (Journal of Information System and Informatics, 2021)
Purpose: This article aims to make strategic planning of information systems and application requirements in health clinics so that they can provide optimally, integrated, and innovative contributions that can unite all supporting aspects in achieving clinical business strategies to increase their competitiveness value in health services in Pagar Alam City. Research Methodology: This article uses a case study at the Klinik Yulia Asniati in Pagar Alam City using the Ward and Peppard strategic planning model. Based on multi-disciplinary literature, the Ward and Peppard Model uses a strategic planning framework and process that includes the external business environment analysis stages using the PEST method, the internal business environment analysis using the value chain method, internal and external IS/IT environmental analysis. Results: This analysis produces an IS/IT strategic planning using McFarlan Strategic Grid Analysis, this stage produces 13 application portfolios that are arranged based on the priority of business needs and information system strategies. Limitations: This article uses the Ward and Peppard model with PEST analysis methods, Michael's Porter value chain, and McFarlan Strategic Grid analysis. This article only uses data and cases at the Klinik Yulia Asniati, Pagar Alam City